Формування творчої особистості педагога у процесі його комунікативної діяльності - Batrynchuk, Zoriana; Костик, Любов Богданівна; Платаш, Л.Б.; Калашнiк Наталія , Kalashnik Nataliia (Вінниця: ВДПУ, 2021)
У статті розкрито проблему комунікації в інформаційному суспільстві. Насамперед, вона стосується освітньої сфери, адже покликана забезпечити всебічну підготовку людини до сучасного життя у світі найрізноманітніших зв’язків, комунікативних можливостей суспільних відносин. Професійна комунікація є основною формою педагогічного процесу, продуктивність якого обумовлюється цілями й цінностями спілкування, прийнятими всіма його суб’єктами за норму індивідуальної поведінки. Розгортається вона у процесі спільної комунікативної діяльності людей (суб’єкт-суб’єктної взаємодії), опосередкованої взаємообміном інформацією, за якої кожен із його учасників засвоює загальнолюдський досвід, суспільні, педагогічні, комунікативні, моральні та інші цінності, знання й способи комунікативної діяльності, виявляє, розкриває й розвиває власні психічні якості, формується як особистість і як суб’єкт комунікації. У цьому сенсі комунікативна діяльність є передумовою формування творчої особистості педагога. The article reveals the problem of communicative opportunities and social relations. First of all, it is related to the educational sphere, because it aims to provide a comprehensive preparation of the person for the modern life in the world of various connections, communicative opportunities of social relations. Professional communication is the main form of the pedagogical process, the productivity of which is determined by the goals and values of communication accepted by all its subjects for the norm of individual behavior. It unfolds in the process of joint communication activities of people (subject-subject interaction), mediated by the exchange of information, in which each of its participants learns human experience, social, pedagogical, communicative, moral and other values, knowledge and ways of communicative activity, identifies, reveals and develops his own mental qualities, is formed as a person and as a subject of communication. In this sense, communicative activity is a prerequisite for the formation of a creative personality of the teacher. Forming a socially active personality requires the use of non-standard forms of pedagogical interaction. One such form is play as a means of developing the creative potential of a future specialist.Game activities perform the following functions: stimulating (arouses interest among students); communicative (mastering elements of communication culture of future specialists); self-realization (each participant of the game realizes its capabilities); developmental (development of attention, will and other mental qualities); entertaining (having fun); diagnostic (detection of deviations in knowledge, skills, behavior); corrective (making positive changes in the personality structure of future professionals). Realization of educational-educational interaction, pedagogical influence of the educator on children is carried out by means of speech, so its specificity significantly influences the effectiveness of the communicative process. Because of this, the culture of broadcasting is an important indicator of a teacher's professionalism. Every teacher must constantly work on improving his or her pedagogical skills, on which the results of his work depend to a great extent. Therefore, it is necessary to pay more attention to the development of speech, to increase the requirements for one's own language culture, to develop the skills of effective communication, oratory.
Keywords: спілкування; творча особистість; комунікативна інтеракція; педагогічна мова вчителя; професійна компетентність; лінгвістика; культура мови